2023
DOI: 10.15605/jafes.038.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Critical Illness-Related Corticosteroid Insufficiency (CIRCI) among Patients with COVID-19 at a Tertiary Hospital: Clinical Characteristics and Outcomes

Abstract: Objectives. Among critically ill patients, there is usually impairment of the hypothalamic-pituitary-adrenal axis, leading to a condition known as critical illness-related corticosteroid insufficiency (CIRCI). This investigation aims to determine the incidence of and characterize CIRCI among patients with COVID-19 as well as to analyze the outcomes of these critically ill patients.Methodology. This is a single-center, retrospective cohort study that investigated the occurrence of CIRCI among critically ill pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In a prospective trial by Bagate et al ( 27 ), only patients who initially failed to meet criteria for extubation were enrolled, and among them, CIRCI occurred in 33% and was associated with a higher likelihood of subsequent extubation failure. In a retrospective study by Arcellana et al ( 32 ), COVID-19 diagnosed with probable or definite CIRCI had longer median days on a ventilator; however, they were all treated with corticosteroids, primarily dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective trial by Bagate et al ( 27 ), only patients who initially failed to meet criteria for extubation were enrolled, and among them, CIRCI occurred in 33% and was associated with a higher likelihood of subsequent extubation failure. In a retrospective study by Arcellana et al ( 32 ), COVID-19 diagnosed with probable or definite CIRCI had longer median days on a ventilator; however, they were all treated with corticosteroids, primarily dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a research study examining the clinical practices and patient outcomes related to CIRCI in patients with refractory shock revealed the existence of a noteworthy threshold that must be exceeded before considering CIRCI as a potential cause of shock. The study also suggested that the apparent underdiagnosis of CIRCI could be attributed to a reduced frequency of steroid administration in cases where there was a justifiable suspicion of CIRCI in patients experiencing shock [ 11 ].…”
Section: Discussionmentioning
confidence: 99%